Emerging roles of ribosome translation in stem cells and stem cell therapy - a review - Yanyan Gao; Linlin Guo; Gaoxiang Shi; Ruifang Wang; Xu’an Wang; Jizhong Lou (Cell & Bioscience)
Abstract Stem cells differ from other somatic cells in that they possess self-renewal and differentiation potential, which endows them with unique characteristics, and have great therapeutic potential. Studies have shown that the self-renewal and differentiation potential of stem cells is regulated by ribosomes during protein synthesis. In this review, we discuss the translation regulation mechanisms and ribosome biogenesis in stem cells. Protein translation levels and ribosome biogenesis change dynamically during the development and differentiation of stem cells, and hierarchical translational regulation promotes stem cell differentiation. We also demonstrate that mitochondrial protein translation plays an important role in the regulation of stem cell fate. Ribosomes not only mediate the self-renewal and differentiation of stem cells through protein synthesis. They are also a key target for stem cell therapy. Understanding the mechanism of ribosome regulation in stem cells will allow better control of stem cells for their application.